Building the Tower of Hanoi with recyclable materials: A methodological proposal for teaching empowerment in Elementary School classes - Paiva, Carlos Daniel Chaves; do Nascimento , Rildo Alves; Santos , Francisco Nordman Costa; Junior , Antonio Francisco de Sales; Alexandre, José Joel; dos Santos, Dayonne Soares; Tomé , Joelder Lincoln Gomes; Cavalcanti , Alisson dos Santos; Tavares , Thayne Freitas; Cavalcante, Cristiane de Oliveira; dos Santos, Cleiton Alves; Rêgo , Flávio Daniel Luz; et al. (Seven Editora, 2024)
This work presents an innovative methodological proposal for the teaching of empowerment in Elementary School II classes, using the construction of the Tower of Hanoi with recyclable materials. The main objective is to facilitate the understanding of mathematical concepts related to empowerment through a practical and playful approach, while promoting awareness of the importance of recycling and sustainability. The methodology involves several steps, starting with the selection and preparation of recyclable materials, which are transformed into components of the Tower of Hanoi game. Then, students actively participate in the construction of the game, which arouses their interest and creativity. During the assembly, concepts of recycling and reuse of materials are discussed, encouraging reflection on sustainable practices in everyday life. After construction, the game is used as a didactic tool to teach potentiation. Practical activities and complementary exercises are developed to reinforce learning, promoting a more contextualized understanding of the concepts involved. Undoubtedly, this approach tends not only to increase student engagement, but also to significantly improve content assimilation. Students are expected to demonstrate greater interest and participation in class, as well as evident progress in understanding empowerment. Another relevant aspect of this proposal is the promotion of interdisciplinarity, integrating knowledge of Mathematics with environmental themes. In conclusion, the methodological proposal of using the construction of the Tower of Hanoi with recyclable materials for the teaching of empowerment proves to be efficient and enriching. It is recommended to continue and expand this type of initiative, exploring other forms of integration between mathematics education and environmental education, aiming at the formation of individuals more prepared for the challenges of the future. DOI:https://doi.org/10.56238/sevened2024.026-006